Effect of new false start rule on start reaction time - Yokokura, S.; Kajiwara, Y.; Hirashita, M.; Tacano, M.; Ito, K.; Nozaki, T. (Pre-olympic Congress 2004. Thessaloniki, Grécia. de 6 a 11 de Agosto de 2004, 2004)
IAAF changed the false start rule from March 2003 that the athlete is disqualified at his 2nd false start. The effects of this change on the starting reaction time are studied here by comparing the past three IAAF world athletic championship games.